Utilization of Mangrove Forest as a Source of Zoology Learning with a Stem Approach - Ruhama Desy M; Sarwi Sarwi; Putut Marwoto; Enni Suwarsi Rahayu; Dyah Rini Indriyanti (International Conference on Science, Education, and Technology, 2021)
The purpose of this article is to present a study of mangrove forest function as a source of zoology learning with a STEM approach. Basically the use of the environment can create something active and effective in the implementation of teaching and learning. Mangrove forest have a variety information related to zoology so that it becomes one way to produce creative learning resources. The presentation of the article is based on 3 aspects, namely (1) Mangrove Forest, (2) Learning Resources, (3) STEM. Literature review or literature study is used as a method of this study, by reviewing scientific journal articles from various reputable publishers. Zoology learning with a STEM approach is one solution in improving the quality of the teaching and learning process, so as to be able to overcome problems that arise from students. STEM is useful for activating student motivation and making students able to think at higher levels. The application of learning involving mangrove forest that have zoological diversity and using the STEM approach can answer obstacles in special zoology learning.